2012
DOI: 10.1038/jcbfm.2012.116
|View full text |Cite
|
Sign up to set email alerts
|

Energy Demand of Synaptic Transmission at the Hippocampal Schaffer-Collateral Synapse

Abstract: Neuroenergetic models of synaptic transmission predicted that energy demand is highest for action potentials (APs) and postsynaptic ion fluxes, whereas the presynaptic contribution is rather small. Here, we addressed the question of energy consumption at Schaffer-collateral synapses. We monitored stimulus-induced changes in extracellular potassium, sodium, and calcium concentration while recording partial oxygen pressure (pO 2 ) and NAD(P)H fluorescence. Blockade of postsynaptic receptors reduced ion fluxes as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 23 publications
2
50
1
Order By: Relevance
“…Yet, even if correct only in order of magnitude, we would conclude that the presynaptic terminal consumes ~1% of the NMJ energy budget. This proportion contrasts starkly with estimates at mammalian central synapses, at which presynaptic energy demands are ~30% of the total synaptic signaling cost [16, 17]. If presynaptic terminals only consume 1% of the NMJ energy budget we suggest that the ability to locomote without fatigue ultimately conferred a greater selection advantage than the energy saved by an efficient terminal, and that as a result low P AZ release sites persisted at the expense of high P AZ sites.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…Yet, even if correct only in order of magnitude, we would conclude that the presynaptic terminal consumes ~1% of the NMJ energy budget. This proportion contrasts starkly with estimates at mammalian central synapses, at which presynaptic energy demands are ~30% of the total synaptic signaling cost [16, 17]. If presynaptic terminals only consume 1% of the NMJ energy budget we suggest that the ability to locomote without fatigue ultimately conferred a greater selection advantage than the energy saved by an efficient terminal, and that as a result low P AZ release sites persisted at the expense of high P AZ sites.…”
Section: Discussioncontrasting
confidence: 67%
“…Initially, total energy demand can be approximated as the sum of the cost of SV release and recycling, and the cost on Ca 2+ extrusion [17, 29]:…”
Section: Part A: the Relationship Between Paz And Ca2+ Influx Per Actmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous [K + ] o and field potential measurements were performed using double‐barrelled ion‐sensitive microelectrodes built according to the protocol described in Liotta et al . (). The Potassium Ionophore I 60031 (Fluka, Buchs, Switzerland) was used accordingly.…”
Section: Experimental Methodsmentioning
confidence: 97%
“…It has been suggested that action potentials have been rendered highly efficient through evolution [10], and thus most of the energy consumed in the brain is used on synaptic activity [3, 10, 11]. The human cortex alone requires approximately 3×10 23 ATP/s/m 3 [1], and the energy expenditure to release one synaptic vesicle is roughly calculated to be 1.64×10 5 molecules ATP [3].…”
Section: Glucose Metabolism: the Bioenergetic Basis For Neurotransmismentioning
confidence: 99%